2015
DOI: 10.1038/leu.2015.253
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of NPM1 mutation-modulated microRNA−mRNA regulation in acute myeloid leukemia

Abstract: Distinct microRNA (miRNA) and mRNA signatures were reported in nucleophosmin (NPM1)-mutated acute myeloid leukemia (AML). However, it remains unknown whether the mutation participates in the dynamic interaction between miRNA and mRNA. In this study, we aimed to investigate the role of NPM1 mutation in modulating miRNA-mRNA regulation (MMR). From the sample-paired miRNA/mRNA microarrays of 181 de novo AML patients, we found that MMR was dynamic and could be affected by NPM1 mutation. By a systematic framework, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Interestingly, MMR could be modulated by NPM1 mutation. Indeed, NPM1 mutation modulated MMR was proposed as a novel prognostic marker in AML [42]. In our current study, we observed distinct miR-10b and KLF4 mRNA signatures in NPM1-mutated AML.…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, MMR could be modulated by NPM1 mutation. Indeed, NPM1 mutation modulated MMR was proposed as a novel prognostic marker in AML [42]. In our current study, we observed distinct miR-10b and KLF4 mRNA signatures in NPM1-mutated AML.…”
Section: Discussionsupporting
confidence: 67%
“…2123 Two large microarray datasets of AML with overall survival (OS) data, including The Cancer Genome Atlas (TCGA) dataset (n=186) 24 and GSE12417 [all with cytogenetically normal (CN) AML; n=162], 25 were utilized to validate the prognostic significance of HOPX . We used TCGA-normalized level-2 intensity and GSE12417 GPL96 data (profiled with Affymetrix Human Genome U133A Array), normalized as described by Metzeler et al .…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis was carried out as described previously; 2123 a brief description is available in the Online Supplementary Appendix .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, expression of ncRNAs is frequently under the control of other players within these networks as well, thereby forming complex circuits which finally orchestrate malignant transformation. Among others, these networks include prominent players in leukemogenesis, such as fms-like tyrosine kinase 3 ( FLT3 ), nucleophosmin ( NPM1 ), CCAAT/Enhancer Binding Protein Alpha ( CEBPA ), tumor protein P53 ( TP53 ) or the RAS-mitogen-activated protein kinase/extracellular signal-regulated kinase (RAS-MAPK/ERK) signaling cascade [19,20,21,22,23]. Lately, the role of ncRNA in mediating sensitivity and resistance to cytotoxic agents, respectively, has been discovered, which makes them attractive targets of novel anti-cancer therapies.…”
Section: Introductionmentioning
confidence: 99%